(untitled) (Fiep Bulletin - online, 2011)
Studies on the production of knowledge in physical education, the analysis made by Gamboa (1982), the University of Brasilia, University of Campinas (1997), at the Pontifical Catholic University of Campinas (1996), research carried out by Silva ( 1997), focused on physical education. The research problem: What are the methodological and epistemological approaches to guide the theses and dissertations of graduate programs in physical education from public universities in the South, from 1999 to 2010? The investigation is characterized by a documentary research literature. As a result of having the preliminary mapping of trends which are in greater evidence, in the South